Borreria savannicola (Spermacoceae, Rubiaceae), a new species from savanna patches within the Caatinga, Ceará State, Brazil - Bezerra De Souza, Elnatan; Nepomuceno, Álvaro; Da Costa Ribeiro, Maria Luiza R.; Miguel, Laila Mabel (Phytotaxa, 2022)
A new species of Borreria from savanna vegetation found within the Caatinga in northwestern Ceará, Brazil, is described and illustrated. Borreria savannicola has an affinity with B. scabiosoides, sharing with it the habitat preference and similar morphological characteristics such as corolla infundibuliform, stigma bilobed and shape of seeds. Nevertheless, the new species differs mainly in its erect habit, linear leaves, terminal glomerule with up to 10 involucral bracts, and obovoid capsule. Images of anatomical characters, electro microphotography of flower, fruit, seed, and pollen, together with photographs of the habitat, distribution map and conservation status are provided.